From Reflection to Sustainability: Mapping Psychological Dynamics, Collective Culture, and Supportive Leadership within Front Office Teams in Hotels - Sustiyatik, Enni; Andjarwati, Tri; Oktavio, Adrie (Journal of Ecohumanism, 2024)
This study investigates the relationships among team psychological safety, participation-supportive leadership, collectivism, team reflexivity, and team sustainability within front office teams in the Indonesian hospitality sector. Utilizing a quantitative research design, data were collected from 387 respondents across major cities, including Surabaya, Jakarta, Denpasar, and Yogyakarta. The findings indicate that higher levels of psychological safety significantly enhance team reflexivity, allowing team members to engage in open communication and collaborative problem-solving. Additionally, participation-supportive leadership fosters an inclusive environment where team members feel empowered to contribute their ideas, which is essential for effective decision-making. Collectivism serves as a moderating factor, influencing the relationship between leadership and team dynamics, thereby highlighting the importance of cultural values in shaping team interactions. The study underscores the necessity of creating a psychologically safe climate that encourages risk-taking and innovation, ultimately leading to improved team sustainability and performance. Limitations include the cross-sectional design, which restricts causal inferences, and the focus on a specific cultural context, potentially affecting the generalizability of the findings. Future research should explore longitudinal designs and incorporate additional cultural dimensions to enhance the applicability of the results. By providing insights into culturally sensitive practices, this study contributes to the understanding of team dynamics and sustainability in organizational settings, particularly within the hospitality industry.